Risky behaviors: Effects of toxorhynchites splendens (Diptera: Culicidae) Predator on the Behavior of Three Mosquito Species - Wan Fatma Atma, Zuharah; Nik, Fadzly; Nur Aishah, Yusof; Hamady, Dieng; Xinzhi, Ni (Library of the University of Arizona, 2015)
Viable biocontrol agents for mosquito control are quite rare, therefore improving the efficacy of existing biological agents is an important study. We need to have a better understanding of the predation-risk behavioral responses toward prey. This research examined prey choices by Toxorhynchites splendens by monitoring the behavioral responses of Aedes aegypti, Aedes albopictus, and Anopheles sinensis larvae when exposed to the predator. The results show that Tx. splendens prefers to consume Ae. aegypti larvae. The larvae exhibited different behavioral responses when Tx. splendens was present which suggest vulnerability in the presence of predators. "Thrashing" and "browsing" activities were greater in Ae. aegypti larvae. Such active and risky movements could cause vulnerability for the Ae. aegypti larvae due to increasing of water disturbance. In contrast, Ae. albopictus and An. sinensis larvae exhibited passive, low-risk behaviors, spending most of the time on the "wall" position near the edges of the container. We postulated that Ae. aegypti has less ability to perceive cues from predation and could not successfully alter its behavior to reduce risk of predation risk compared with Ae. albopictus and An. sinensis. Our results suggest that Tx. splendens is a suitable biocontrol agent in controlling dengue hemorrhagic vector, Ae. aegypti.